2018
DOI: 10.1186/s12870-018-1425-z
|View full text |Cite
|
Sign up to set email alerts
|

A Lotus japonicus E3 ligase interacts with the Nod Factor Receptor 5 and positively regulates nodulation

Abstract: BackgroundPost-translational modification of receptor proteins is involved in activation and de-activation of signalling systems in plants. Both ubiquitination and deubiquitination have been implicated in plant interactions with pathogens and symbionts.ResultsHere we present LjPUB13, a PUB-ARMADILLO repeat E3 ligase that specifically ubiquitinates the kinase domain of the Nod Factor receptor NFR5 and has a direct role in nodule organogenesis events in Lotus japonicus. Phenotypic analyses of three LORE1 retroel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…The recognition of NF from compatible rhizobia is a crucial step for root nodule symbiosis. Two NF receptor (NFR) genes or their orthologs were identified and characterized in several legumes with root hair infection [18][19][20][21][22][23][24]. These NFR genes were named NFR1 and NFR5 in L. japonicus, both encoding LysM-type serine/threonine receptor kinases [19].…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of NF from compatible rhizobia is a crucial step for root nodule symbiosis. Two NF receptor (NFR) genes or their orthologs were identified and characterized in several legumes with root hair infection [18][19][20][21][22][23][24]. These NFR genes were named NFR1 and NFR5 in L. japonicus, both encoding LysM-type serine/threonine receptor kinases [19].…”
Section: Introductionmentioning
confidence: 99%
“…LjPUB13 is an E3 ligase that interacts with and ubiquitinates LjNFR5 in vitro (Tsikou et al, 2018). Thus, the biological role of LiPUB13 in promoting rhizobial symbiosis may be similar to that of NopM, as both proteins can ubiquitinate LjNFR5.…”
Section: Discussionmentioning
confidence: 99%
“…Once NF signaling is initiated, protein turnover and signaling activity of NFRs may be critical for maintaining proper symbiotic signaling and subsequent rhizobial infection. Previous research demonstrated that mutation in the LjPUB13 gene suppresses nodulation in L. japonicus (Tsikou et al, 2018). LjPUB13 is an E3 ligase that interacts with and ubiquitinates LjNFR5 in vitro (Tsikou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Host plants secrete flavonoids, inducing rhizobia to synthesize and secrete Nod factors (NFs), a type of lipo-chitooligosaccharide molecules [ 1 , 2 ]. Two plant LysM-type serine/threonine receptor kinases, NFR1 and NFR5 in Lotus japonicus (Nod Factor Receptor 1 and 5) [ 3 , 4 , 5 ], cooperating with the leucine-rich repeat (LRR) receptor-like kinase SymRK (Symbiosis Receptor-like Kinase) [ 6 ], recognize NFs and initiate the NF signaling pathway [ 7 , 8 , 9 , 10 ]. The core component of the NF signaling pathway is a calcium oscillation which is decoded by the nucleus-localized CCaMK (calcium/calmodulin-dependent protein kinase) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%